PastorC-Tambo: a simplified model to assess carbon balance of dairy farms - Zurbriggen, Gabriel Alberto; Piazza, A.M.; Montico, Sergio; Garcia, Karina Elizabet; Galli, Julio Ricardo (Ediciones INTA, 2024)
Grazing systems have the potential to mitigate greenhouse gas (GHG) emissions and improve C balance through soil C sequestration. The inclusion of soil organic carbon (SOC) balance in farm scale models is needed to assess the C balance of grazing dairy systems. The objective of this work was to present and evaluate the sensitivity of a simplified model developed to estimate C balance of dairy production systems in the Pampas region of Argentina. The model, called PastorC-Tambo, combines three interrelated sub-models: a sub-model of dry matter intake (DMI), a sub-model of GHG emissions, and a sub-model of SOC balance. To assess the sensitivity of the model, different forage productivities (high: 18, 7.5, and 27 t DM/ha, medium: 12, 5 and 18 t DM/ha, and low: 6, 2.5, and 9 t DM/ha for alfalfa, oat, and maize silage, respectively), concentrate supplementation levels (350, 250, and 150 g/l milk for high, medium, and low, respectively), stocking rates (from 0.27 to 3.56 cows/ha, with use efficiencies of 25, 45, 65, and 85%), effluent treatment system, and milking time, were simulated for representative dairy production systems. C balance estimates ranged between -2.54 and 0.64 t C/ha. Balance improved with the rise in forage productivity and declined as stocking rates increased. Increased concentrate supplementation improved C balance at constant forage productivity and stocking rate. Effluent treatment systems also affected C balance. Storage in anaerobic lagoons had the lowest C balance, while the inclusion of solids separation and agronomic reuse improved it. Anaerobic digestion also increased the C balance compared to anaerobic lagoons. PastorC-Tambo proved to be sensitive to changes in the C balance of commercial dairy farms in the Pampas region of Argentina.